The dynamic implementation of non-overt arguments in nominalizations - Camacho, Roberto Gomes [UNESP] (My University, 2007)
Valency is an inherent property of nominalizations representing higher-order entities, and as such it should be included in their underlying representation. On the basis of this assumption, I postulate that cases of non-overt arguments, which are very common in Brazilian Portuguese and in many other languages of the world, should be considered a special type of valency realization. This paper aims to give empirical support to this postulate by showing that non-overt arguments are both semantically and pragmatically motivated. The semantic and pragmatic motivations for non-overt arguments may be accounted for by the dynamic implementation of the FDG model. I argue that the way valency is realized by means of non-overt arguments suggests a strong parallelism between nominalizations and other types of non-finite embedded constructions – like infinitival and participial ones. By providing empirical evidence for this parallelism I arrive at the conclusion that there are at least three kinds of non-finite embedded constructions, rather than only two, as suggested by Dik (1997).
Keywords: Nominalization; Embedded Constructions; Valency; Overt Argument; Non-Overt Argument